Inovasi Pembelajaran Jarak Jauh Sebagai Upaya Dalam Meningkatkan Literasi Siswa - Inyong J. M. Be’y; Nurdin (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
This study aims to analyze distance learning innovation as an effort to improve students’ literacy at SMA Negeri Sabun. This research employs a qualitative approach, using data collection techniques such as observation, interviews, and documentation. The research subjects consist of one teacher and two students selected purposively. The findings indicate that digital-based distance learning innovation enhances students’ active participation in the learning process. Teachers play a crucial role in designing interactive learning strategies, providing constructive feedback, and utilizing engaging digital media. This encourages students to become more independent, critical, and creative in accessing and processing information. Furthermore, distance learning offers flexibility in time and access to various learning resources, enriching students’ learning experiences. However, several challenges remain, including limited internet access and limited technological skills. Overall, distance-learning innovation has proven effective in improving students’ literacy, including reading, writing, and digital literacy.